Metrics for performance measurement of a reverse/closed-loop supply chain. (2nd June 2009) - Pochampally, Kishore K.; Gupta, Surendra M.; Govindan, Kannan
Many a firm today continually evaluates the performance of its supply chain in order to check whether the supply chain needs to be re-designed with respect to the customers' needs and requirements. Due to the inherent differences in a traditional supply chain and a reverse/closed-loop supply chain with respect to movement of goods as well as information, it is inappropriate to adopt the performance measures of a traditional supply chain for a reverse/closed-loop supply chain. To this end, this paper addresses the metrics that help evaluate the performance of a reverse/closed-loop supply chain. These metrics are incorporated in a mathematical model that uses quality function deployment (QFD) and linear physical programming (LPP) effectively to measure the 'satisfaction level' of the supply chain with respect to each of the metrics. The approach is illustrated through a numerical example. Brief introductions to the techniques used (QFD and LPP) and a brief review of the research in the field of strategic planning of a reverse/closed-loop supply chain are also given.